Establishment of in vitro Three-Dimensional Human Brown Adipose Tissue-like Constructs. - Zhao, Nan. (2017)
Abstract: Obesity has become a worldwide pandemic and there is an urgent need to develop efficient anti-obesity therapies. Recent studies suggested that brown adipose tissue, which plays a key role in thermogenesis, has potential to combat obesity. The aim of this study was to establish a physiologically relevant human brown adipose tissue-like construct in vitro as a first step toward studies with this tissue related to potential treatments for obesity. We successfully obtained the three-dimensional (3D) brown fat-like constructs by seeding human adipose derived stem cells (hASCs) onto porous silk sponge scaffolds, and treated the 3D constructs with media containing a cocktail of brown adipose tissue (BAT) inducer. After 6 weeks of culture the cells on the scaffolds were uncoupling protein 1(UCP1)-positive, rich in mitochondria, and filled with multi-locular lipid droplets, all hallmarks of brown adipocytes. We believe that with further characterization as well as functional analysis, the 3D brown fat-like tissue has the potential to be useful as an in vitro platform for exploring human brown adipose tissue functions. In future work, this tissue may also serve as a tissue-engineering based therapy for in vivo implantation as a new anti-obesity approach.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Biomedical Engineering.; Advisor: David Kaplan.; Committee: David Kaplan, Qiaobing Xu, and Kyongbum Lee.; Keyword: Biomedical engineering.